2017
DOI: 10.1515/ngoe-2017-0009
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study Regarding Radical Innovation, Research and Development Management, and Leadership

Abstract: The objective of this research is to empirically compare the management that is most suitable for radical innovation with that needed for incremental innovation. The relationship between the results of research and development and management styles was surveyed using a questionnaire. Respondents included research and development leaders in Japanese manufacturing, with special attention given to the differences between radical innovation and incremental innovation. Results verified, in an integrated way, the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In innovation literature, several studies (Abd Aziz and Samad, 2016;Afraz et al, 2021;Ali, 2021;Liu, 2017) discussed the relationship between innovation and competitive advantage. Isada and Isada (2017) demonstrated that innovation could be divided into two basic types according to its novelty, namely, radical innovation and incremental innovation. Radical innovation involves significant improvements in products and services and the provision of new products and services (Nguyen, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In innovation literature, several studies (Abd Aziz and Samad, 2016;Afraz et al, 2021;Ali, 2021;Liu, 2017) discussed the relationship between innovation and competitive advantage. Isada and Isada (2017) demonstrated that innovation could be divided into two basic types according to its novelty, namely, radical innovation and incremental innovation. Radical innovation involves significant improvements in products and services and the provision of new products and services (Nguyen, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In maintaining a competitive advantage, companies will spend optimal effort to manage the capital cost in order to be able to develop new service innovation (Hertog et al, 2010;Aujirpongpan & Hareebin, 2020), and must try to understand behavioral and social element to classify SCO (supply chain orientation) individually and organizationally so that the company can operate efficiently (Lee & Nam, 2016;Sillanpää, 2015). While resource-oriented companies will be able to increase radical innovation, so that they can develop unique resources and find environment opportunity that can be exploited (Reulink, 2012), beside needing to consider leadership, management, and entrepreneurial orientation aspects (Isada & Isada, 2017;Shih, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The strategic orientation of the company toward the market can be described as strategic direction run by company to create the proper behavior in the increase of continuous superior performance (Isada & Isada, 2017;Shih, 2018). Similarly, strategic orientation that is focused on customers are organizational culture that facilitates the understanding of targeted buyers and possible continuous creation of customer value (Wirtz & Daiser, 2018;Khadka & Maharjan, 2017), and benefits chosen by customers (Sakyi-Gyinae & Holmlund, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Slater, Mohr, and Sengupta (2014) held that among various antecedents, leadership behavior is the primary one to promote radical innovation and a leader's cognitive and behavioral characteristics in different situations can significantly affect behavior intentions of organizations, teams, and employees. In addition, Isada and Isada (2017) alluded that leadership behaviors can influence radical innovation through R&D culture management and other factors. Moreover, leadership and innovation occur at all three levels of individuals, teams, and organizations (Robledo, Peterson, & Mumford, 2012).…”
mentioning
confidence: 99%